The Centenary of the Journal Soil Science: Reflections on the Discipline in the United States and Russia Around a Hundred Years Ago. Issue 6 (June 2017) - Moon, David; Landa, Edward R.
Abstract : ABSTRACT: Soil Science emerged on the scene in January 1916 as a journal focused on soil fertility and allied fields. Its founding editor and guiding force for 23 years was Jacob Goodale Lipman, an immigrant from the Russian Empire who came to the United States in his teens and received all of his scientific training in the United States, at Rutgers and Cornell Universities. His knowledge of the Russian language and culture, rather than a preexisting professional network, however, enabled him to serve as an important bridge to the Russian soil science community. As well as facilitating communication between soil scientists in the United States and the Russian Empire (and, after 1917, its successor state, the Soviet Union), Lipman also found support for young scientists from abroad to come to work at Rutgers. The most prominent was another migrant from the Russian Empire who went on to win a Nobel Prize, Selman A. Waksman. Lipman, who had an enormous capacity for work, also organized the first International Congress of Soil Science in Washington, DC, in 1927, which was followed by a remarkable transcontinental excursion. These events allowed many American and international, including Soviet, soil scientists to meet. However, the journal that he guided from its foundation in 1916 provided a longer-term vehicle for international intellectual exchange before and after 1927.